Influence of the state of the local system of nonspecific protection the oral fluid on clinical periodontal status indicators - V. A. Akopova; I. M. Bykov; N. V. Lapina; L. A. Skorikova; N. I. Bykova (Кубанский научный медицинский вестник, 2015)
The relationship of periodontal disease and somatic pathology determines the interest of the dentist to the peculiarities of the local organization of nonspecific protection and the search for new ways of non-invasive diagnosis and monitoring for violations of its operation, coupled with the presence of foci of chronic inflammation in the oral cavity and the possibility of development or worsening of the clinical course of the underlying disease. One of the main components of nonspecific protection of organs and tissues are immunological reactivity and antioxidant system, the sustainability of living cells to infection and free radical damage.